Exploring movement decisions: Can Bayesian movement‐state models explain crop consumption behaviour in elephants (Loxodonta africana)?. Issue 4 (15th February 2020) - Vogel, Susanne Marieke; Lambert, Ben; Songhurst, Anna Catherine; McCulloch, Graham Paul; Stronza, Amanda Lee; Coulson, Tim
Abstract: Animal movements towards goals or targets are based upon either maximization of resource acquisition or risk avoidance, and the way animals move can reveal information about their motivation. We use hidden Markov models (HMMs) fitted in a Bayesian framework and hourly Global Positioning System fixes to distinguish animal movements into distinct states and analyse the influence of environmental variables on being in, and switching to, a particular state. Specifically, we apply our models to understand elephant movement decisions around agricultural fields, and crop consumption. As it is unclear what the role of habitat features are on this complex process, we analyse whether elephants target agricultural crops for consumption, or simply pass through them in search of water. Our HMMs separate elephant movements into two states: exploratory movements that are fast and directional, and encamped movements that are slow and meandering. For each elephant, we ran 16 models with each possible combination of selected habitat features (river, elephant corridor, agricultural field, trees), and repeated these analyses including interaction effects with both season and time of day. We used cross‐validation to select the best model. In corridors, exploratory movements are dominant. Elephants mainly showed encamped movements at the river during the dry season, when temporary water sources have dried out and elephants relied on this permanent water source. In fields, males most often exhibited exploratory movements to and from the river, while females showed an increase in the frequency of encamped behaviour during the dry season and at night—the times when most crop consumption and movements through fields occur. Adaptation to risk could explain this behaviour, since foraging in fields is likely less risky under the cover of darkness and during the dry season when farmers are absent. This sex segregation in elephant movement decisions highlights the importance of predation risk in shaping movement patterns, which can result in sex segregation in responses to mitigation methods. The increase in encamped movements in the dry season suggests the importance of agricultural timing, and shows the potential for early ploughing and early‐harvest crop types in order to reduce elephant crop consumption. Taking this into account could increase efficiency of elephant crop consumption mitigation. Abstract : The authors study is a novel application of hidden‐Markov movement models to address an urgent conservation issue: elephant crop consumption in the Okavango delta, Botswana. By translating a large data‐set of elephant Global Positioning System collar data into types of movement states, the authors observe elephant responses to habitat features, such as agricultural fields. The results show that elephants do not appear to target fields for foraging, yet that female elephants increase in movement states associated with foraging when they run less risk of encountering humans. This risk avoiding behaviour by female elephants supports the predator risk hypothesis in elephant crop consumption.